Representasi Maskulinitas Dalam Serial Piecky Bliendiers Kajian Dengan Perspektif Raline Conell - Amanad Shabil; Aswandikari; Johan Mahyudi (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
The representation of masculinity in the Peaky Blinders Season 1 series is examined from Raewyn Connell's perspective. This research shows that this series represents masculinity through male characters, which include traits such as physical strength, dominance, and violence. This analysis uses Connell's theory of masculinity to identify how the series constructs and represents the concept of masculinity in a social and cultural context